x² − 6x + 7 = 0
Let's complete the square [x²-6x+(??)²] -(??)² +7 = 0
As you noticed we have added the unknown square & also subtract the same so that not to change the equation
The question now is to calculate this square (??)²
We know that the middle term (6x) is twice the square root of the 1st times the square root of the 2nd, That is 6x=2x (multiply) √(??)²
6x = 2x?? & ??=6x/2x===> ?? =3 & (??)² =9
Hence plug (??)² into the equation above:
x² - 6x + 9 - 9 +7 =0
(x²-6x+9) -9 + 7 =0
(x-3)² -2 =0 ====> (x-3)² = 2 (that is B)